Size-dependent strong metal-support interaction in TiO2 supported Au nanocatalysts - Xiaorui Du (Nature Portfolio, 2020)
Strong metal-support interaction (SMSI) is critical in determining the catalytic performance of supported metal catalysts. Here the authors report a phenomenon of size-dependent classical SMSI in Au/TiO2 catalyst where larger Au particles are more prone to be encapsulated than smaller ones.